2016
DOI: 10.5271/sjweh.3561
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of objectively measured physical activity and sedentariness among blue-collar work using survey questionnaires

Abstract: Refers to the following text of the Journal: 2007;33(6):401-480The following article refers to this text: 2018;44(2):111-223

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 47 publications
3
28
0
Order By: Relevance
“…The use of objective technical measurements of physical activity is a clear strength of the current study as it allows precise exposure estimates while minimizing potential bias associated with self-reported measures of physical activity [33]. Since the use of activity classification from multiple accelerometers is a rather novel approach in observational studies, comparisons with current recommended guidelines for time and intensity of physical activity are limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of objective technical measurements of physical activity is a clear strength of the current study as it allows precise exposure estimates while minimizing potential bias associated with self-reported measures of physical activity [33]. Since the use of activity classification from multiple accelerometers is a rather novel approach in observational studies, comparisons with current recommended guidelines for time and intensity of physical activity are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Objective measurements of physical activity are crucial for obtaining precise exposure estimates and minimize potential bias associated with self-reported measures of physical activity [33]. Moreover, because OPA and LTPA are correlated with socio-economic position, effect modification and confounding by socio-economic factors are an issue in the investigation of LTPA, OPA and health.…”
Section: Introductionmentioning
confidence: 99%
“…An attractive option is to correct for self-report bias in a calibration procedure and use the corrected exposure values for further analyses. Calibration, or exposure modeling, is an established method for correcting self-reported information in the field of nutritional and body composition (41,42) and in occupational hygiene (43)(44)(45), and it is becoming increasingly popular in the field of physical activity (46)(47)(48)(49), even in an occupational context (50)(51)(52). The present study contributes to the development of effective models for estimating "true" sedentary time and time in MVPA by identifying a number of factors that may, in addition to the self-reported exposure in its own right, influence the extent of self-report bias, and that may, therefore, be candidates for inclusion in calibration models.…”
Section: Gupta Et Almentioning
confidence: 99%
“…Self-reported total sitting time, work and leisure combined, has been shown to be underestimated by 15−37% (15,16), while underestimation ranged from 1.5−43% among workers selfreporting their occupational sitting time (17,18). Bias in self-reported sitting time may vary depending on the worker's body mass index (BMI) (17,19,20), gender (17,19,21), age (19,22), musculoskeletal pain (17,21), psychosocial work demands (17), and education level (22). Bias in self-reported sitting time will result in flawed relations with health outcomes, while nondifferential misclassification (eg, as a result of random variation in self-reported sitting time) can result in attenuation of associations with health outcomes (23).…”
mentioning
confidence: 99%
“…Other studies have developed models to improve self-reported sedentary behavior using objective measurements as an estimate of the 'truth' (13,14). Thus far, only few studies have, however, addressed self-reported sitting at work (17,19,21). All these occupational studies were based on blue-collar workers, while models developed for office workers are lacking.…”
mentioning
confidence: 99%